(untitled) (Eurasian Journal of History, Geography and Economics, 2023)
The aim of the research is to employ one of the important techniques of artificial intelligence, which is fuzzy logic in the field of auditing, and to explore how to benefit from this technology in enhancing auditing procedures. This questionnaire consisted of (50) questions and two axes, the first axis is dedicated to measuring audit procedures and includes three dimensions, and the second axis is dedicated to measuring fuzzy logic, and the five-point Likert scale was used. The results showed that there is a direct effect between each paragraph and the dimension to which it belongs.